Effect of Screw Insertion Torque on Mechanical Properties of a Hybrid Polyaxial Locking System - Jung, Hye-Jin; Jang, Aram; Yim, Hyeong-Jun; Han, Chang-Hoon; Lee, Jae-Hoon (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to determine the effect of insertion torque and angulation on the push-out strength of screws in Atraumatic Rigid Fixation (ARIX) system.Materials and Methods In vitro mechanical tests of the ARIX system were conducted. Screw plate constructs (n = 120) were tested using five different insertion torques at four different angles relative to the perpendicular axis of the plate. Before the push-out test, screws were locked into the plates, and the push-out force of the screw was measured by applying a load parallel to the screw axis.Results Implant failure was observed at 0.8 Nm at an insertion angle of 15 degrees, and at 1 Nm at 0 degree, 5 degrees and 10 degrees. Two types of failures were observed: cold welding and plate deformation. An insertion torque of 0.8 Nm produced a significantly higher push-out force compared with 0.2 Nm. Non-angled specimens with 0.8 Nm insertion torque exhibited significantly higher screw push-out forces compared with other tested specimens and insertion angles. Insertion angle did not affect screw push-out force at insertion torques of 0, 0.2, 0.4 and 0.6 Nm.Conclusion The ARIX locking system is much more sensitive to insertion torque than angle. An effect of insertion angle was observed only at an insertion torque of 0.8 Nm, under which all angles significantly decreased push-out force relative to zero degrees of angulation. In addition, low insertion torques can result in screws loosening over time, while greater insertion torques than 1 Nm can result in screw head stripping and plate hole deformation.
Keywords: polyaxial locking plate; implant failure; insertion torque; insertion angle; push-out test